House price cycles in Europe - Stefano Corradin; Alessandro Fontana (European Central Bank (ECB), 2013)
This paper examines the house price dynamics for thirteen European countries. A Markov-switching error correction model is estimated on house price returns at the country level, with deviations between house prices and fundamentals feeding into the short-run dynamics. The system is assumed to be in either a stable regime, in which deviations from the long-run equilibrium tend to vanish over time, or in an unstable regime, in which no such correction takes place. The analysis yields three sets of results. First, house price returns in Europe are generally characterized by three (high, medium and low) phases; growth rates within regimes differ largely across countries. Second, for some European countries the observed high growth phases are associated with a stable regime. Third, European housing markets have been more in sync with each other since 2000 following a growing trend in the time-span 2002-2006 and a dramatic downturn after the Lehman collapse in 2008 and during the Euro area sovereign debt crisis.
Keywords: G12; R11; R31; 330; house prices; Markov-switching and error-correction models